Paracoccidioidomycosis in Japan report of a case - Chikamori, Taishiro; Saka, Satoshi; Nagano, Hiroshi; Saeki, Shigeru; Lacaz, Carlos da Silva; Rodrigues, Maria Conceição; Cassaguerra, Cintia Marzagão; Braccialli, Maria Luisa (Revista do Instituto de Medicina Tropical de São Paulo, 1984)
The Authors report a non-autochthonous case of paracoccidioidomycosis in Tokyo, the second related in Japan. The patient lived for nearly five years in the urban area of São Paulo, where probably she acquired the primary infection. There was no history of corticoid therapy or other diseases that could explain paracoccidioidomycosis. Three years after her return to Japan, she presented lymphadenopathy, hepatosplenic involvement and absence of pulmonary lesions. The present case, with histopathological examination and culture positive to Paracoccidioides brasiliensis also showed compatible serological results. The blastic feature of bone lesions, rare in ribs in this mycosis, as well as the generalized lymphadenopathy are discussed. Treatment with amphotericin B and ketoconazole offered good results. In this paper the Authors discuss the problem of the "pathology of importation" with its implications.